‘Whose Education Is It Anyway?’ - Ra Davis (New Zealand Journal of Teachers' Work)
Teachers need to understand the economic and global contexts that underpin the curriculum because they impact on the interpretation, definition and perception of their role. Grundy (1994) maintains that there is a “… taken for granted view of the curriculum as something that is given to, or provided for, students” (p.27). This view of curriculum fails to acknowledge the crucial, dynamic role that teachers and students bring to the active construction of knowledge. Teachers need to be prepared to understand the ideologies underpinning the curriculum that they interpret and deliver. They should be aware of the reconstruction of knowledge and the changing values that they impart through the delivery of the curriculum. The politicisation of education directly affects teachers. This new alternative concept of teaching is changing the role of teachers from professional contextualists to that of technocratic reductionists (Codd, 1998).